Fuel properties of biodiesel produced from different raw materials in Croatia - Voća, Neven (Strojniški vestnik, 2008)
During the past decade or even earlier almost all the EU countries, as well asmost transition countries, launched the production of biodiesel fuel. Such atrend will continue in the future as it is indicated in the EU Directive (2003/30/EC) on alternative fuels for road transport and measures for promotion of the use of biodiesel. In Croatia, the production of biodiesel started only in 2005. It is based on raw materials which are available in the domestic environment: rapeseed oil and sunflower oil and waste edible oil. Methyl ester produced from rapeseed oil fully meets the EU standard under EN 14214, i.e., quality requirements for biodiesel fuel and may be used as pure (B100) or blended with mineral diesel fuels. Since methyl ester of sunflower oil and waste edible oil in some parameters do not meet the mentioned requirements, it is recommended to use them either as blended with rapeseed methyl ester or blended with mineral diesel fuel, which conforms to the recommendation of the European Union Strategy for biofuels production COM (2006).
Keywords: goriva; biodizel; proizvodnja; Croatia; Hrvaška